1990
DOI: 10.1042/bj2700265
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of reduced cellobiose oxidase with oxygen. Is cellobiose oxidase primarily an oxidase?

Abstract: We report rapid-mixing experiments in which cellobiose oxidase, fully reduced with cellobiose, is allowed to react with excess molecular O2. Analysis of the progress curves and their comparison with computer simulations suggests that O2 reacts only with the cytochrome b-type haem and with a rate constant of approx. 0.5 s-1. In steady state the cytochrome b is partially oxidized, whereas the flavin remains largely reduced. This situation may be contrasted with that when dichloroindophenol is substituted for O2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 4 publications
1
19
1
Order By: Relevance
“…Several recent reports [5,10,11] suggest that atmospheric oxygen is a poor electron acceptor for CBO, contrary to its nomenclature. The in vivo electron aceeptor for CBO still seems to be unknown.…”
Section: Discussionmentioning
confidence: 92%
“…Several recent reports [5,10,11] suggest that atmospheric oxygen is a poor electron acceptor for CBO, contrary to its nomenclature. The in vivo electron aceeptor for CBO still seems to be unknown.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast to Morpeth's semiquinone suggestion [68], Wilson et al [85] identified the haem group as a candidate site. Later, the same group [63] redefined (for P. chrysosporium CDH) the relationships, arguing for the flavin as the site of oxygen reduction to superoxide, and the haem as a site of superoxide reduction to peroxide.…”
Section: Formation Of Reactive Oxygen Speciesmentioning
confidence: 97%
“…The haem group is bound in a pocket at one face of the β sandwich close to the surface of the molecule. The concave inner β sheet forms the framework of the pocket, and three loops protruding from this sheet wedge the protoporphyrin-IX ring, two from above (residues 62-68 and 148-161) and one from below (residues [85][86][87][88][89][90][91][92][93][94][95]. The packing of the pocket is tight with mainly hydrophobic residues, leaving little or no space for entry of additional molecules.…”
Section: Overall Structure Of the Cdh Cytochrome Domainmentioning
confidence: 99%
“…The haem then acts merely as a parking place for extra electrons when one‐electron acceptors oxidise the flavin (the ‘electron sink’ model). In contrast Wilson et al [12] suggested that even the two‐electron acceptor, oxygen, may actually react with the haem group rather than the flavin.…”
Section: Introductionmentioning
confidence: 99%